2021
DOI: 10.3389/fimmu.2021.761475
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Vascular Protective and Immune Supportive Sphingosine-1-Phosphate During Cardiac Surgery

Abstract: IntroductionSphingosine-1-phosphate (S1P) is a signaling lipid and crucial in vascular protection and immune response. S1P mediated processes involve regulation of the endothelial barrier, blood pressure and S1P is the only known inducer of lymphocyte migration. Low levels of circulatory S1P correlate with severe systemic inflammatory syndromes such as sepsis and shock states, which are associated with endothelial barrier breakdown and immunosuppression. We investigated whether S1P levels are affected by steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Studies have shown that the operative time is associated with POAF, and a longer operative time may lead to more severe atrial ischemia and inflammation, which is more likely to induce POAF [ 18 ]. Off-pump theoretically reduces the inflammatory response and myocardial injury in patients [ 19 ], and this opinion was confirmed by Fan et al[ 14 ] In this study, the usage rate of cardiopulmonary bypass in POAF group is higher than non-POAF group (11.3% v.s. 8.5%).However, there was no significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 75%
“…Studies have shown that the operative time is associated with POAF, and a longer operative time may lead to more severe atrial ischemia and inflammation, which is more likely to induce POAF [ 18 ]. Off-pump theoretically reduces the inflammatory response and myocardial injury in patients [ 19 ], and this opinion was confirmed by Fan et al[ 14 ] In this study, the usage rate of cardiopulmonary bypass in POAF group is higher than non-POAF group (11.3% v.s. 8.5%).However, there was no significant difference between the two groups.…”
Section: Discussionsupporting
confidence: 75%
“…Subtype 1 (S1P1) is required in the protection of endothelial barrier function, whereas the activation of S1P2 and S1P3 receptors disrupts the endothelial barrier. Pharmacological activation of the S1P1 receptor with FTY-720 and SEW2871 preserved vascular function in rats on CPB [238] and might be an interesting target to protect both the vasculature and the heart as low circulating levels of S1P were found in cardiac surgery patients [239].…”
Section: Endothelial Barrier Functionmentioning
confidence: 99%